2011
DOI: 10.1111/j.1467-8624.2011.01626.x
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and Outcomes of Joint Trajectories of Mother–Son Conflict and Warmth During Middle Childhood and Adolescence

Abstract: This study investigated the development of mother-son relationship quality from ages 5 to 15 in a sample of 265 low-income families. Non-parametric random effects modeling was utilized to uncover distinct and homogeneous developmental trajectories of conflict and warmth; antecedents and outcomes of the trajectory groups also were examined. Four conflict trajectory groups and three warmth trajectory groups were identified. Difficult temperament in early childhood discriminated both conflict and warmth trajector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
78
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 67 publications
(87 citation statements)
references
References 55 publications
8
78
0
1
Order By: Relevance
“…Each item was rated on a five-point Likert scale (1 = definitely not; 2 = not really; 3 = not sure; 4 = somewhat true; 5 = definitely true). A previous study using both the warmth/openness and conflict subscales of the ACRS has shown them to be predictive of later antisocial behavior and social skills (Trentacosta et al, 2011). In the current sample, the warmth/openness subscale had acceptable internal consistency at age 3 ( α = .68).…”
Section: Methodsmentioning
confidence: 99%
“…Each item was rated on a five-point Likert scale (1 = definitely not; 2 = not really; 3 = not sure; 4 = somewhat true; 5 = definitely true). A previous study using both the warmth/openness and conflict subscales of the ACRS has shown them to be predictive of later antisocial behavior and social skills (Trentacosta et al, 2011). In the current sample, the warmth/openness subscale had acceptable internal consistency at age 3 ( α = .68).…”
Section: Methodsmentioning
confidence: 99%
“…The chronically high and high decreasing conflict groups demonstrated higher rates of antisocial behaviors at age 15 compared to the moderate and low conflict groups, suggesting that how conflict changes over time differentially impacts adolescent problem behavior. Taken together, the work of Burt et al [16], Klahr et al [19], and Trentacosta et al [15] suggests that the presence of elevated parent–child conflict during the school-age period and early adolescence is related to later child behavior problems. Investigating co-occurring parent–child conflict and child maladjustment during early childhood has the potential to shed light on how these processes unfold together when both the parent–child relationship and children’s repertoire for responding to interpersonal conflict are rapidly developing.…”
Section: Introductionmentioning
confidence: 99%
“…Similarities between parent–child conflict and harsh parenting include the expression of negative parental affect, intrusive behaviors, and even aggression [812]. In contrast, parent–child conflict is comprised of mutual negative behaviors of both the parent and child (e.g., [1315]). Whereas there are similarities in parenting behaviors in both constructs, the review below focuses primarily on studies of parent–child conflict where both parent and child behavior have been explicitly considered, especially those studies focusing on parent–child coercive processes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations